Chemical modification of pristine carbon nanotubes and their exploitation as the carbon hosts for lithium-sulfur batteries. (21st December 2016) - Chen, Liang; Zhou, Haihui; Fu, Chaopeng; Chen, Zhongxue; Xu, Chenxi; Kuang, Yafei
Abstract: In this work, we prepared nitrogen-doped open-ended carbon nanotubes (N-O-E-CNTs) through controllable chemical cutting followed by a facile hydrothermal process. Scanning electron microscopy, X-ray diffraction, Raman and some other techniques were used to characterize the as-prepared N-O-E-CNTs, which possessed enhanced specific surface area and pore volume, and excellent conductivity. The N-O-E-CNTs were investigated as carbon host for Li–S batteries by cyclic voltammetry, galvanostatic charge/discharge and electrochemical impedance, and the electrochemical testing showed that the N-O-E-CNTs/S cathode presented much better cyclability and rate capability than the carbon nanotubes (CNTs)/S and open-ended carbon nanotubes (O-E-CNTs)/S cathodes. The main reasons for the improved performance were explained as follows. On one hand, the controllable chemical cutting for CNTs can effectively increase the specific surface area and pore volume while retaining good conductivity, and the formed open-ended structure is beneficial to trapping sulfur species in the internal nanotube cavity. On the other hand, the N doping for the N-O-E-CNTs can not only recover the conductivity, but also enable the N-O-E-CNTs to possess more superior compatibility and adsorbability for sulfur species, resulting in high utilization of active material and effective alleviation of polysulfides shuttling. Graphical abstract: Controllable chemical cutting and successful N doping endow N-O-E-CNTs with enhanced specific surface area as well as pore volume, good conductivity and excellent compatibility and adsorbability for sulfur species, which renders them as a superior carbon host for Li–S batteries. Highlights: N-O-E-CNTs were prepared by chemical cutting followed by hydrothermal process. Chemical cutting increases the specific surface area while keeping good conductivity. N doping endows N-O-E-CNTs with good compatibility and adsorbability for sulfur. The N-O-E-CNTs/S cathode shows excellent cyclability and rate capability.